If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1(x + 5) = 2(x + 3) + -7 Reorder the terms: 3 + -1(5 + x) = 2(x + 3) + -7 3 + (5 * -1 + x * -1) = 2(x + 3) + -7 3 + (-5 + -1x) = 2(x + 3) + -7 Combine like terms: 3 + -5 = -2 -2 + -1x = 2(x + 3) + -7 Reorder the terms: -2 + -1x = 2(3 + x) + -7 -2 + -1x = (3 * 2 + x * 2) + -7 -2 + -1x = (6 + 2x) + -7 Reorder the terms: -2 + -1x = 6 + -7 + 2x Combine like terms: 6 + -7 = -1 -2 + -1x = -1 + 2x Solving -2 + -1x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + -1x + -2x = -1 + 2x + -2x Combine like terms: -1x + -2x = -3x -2 + -3x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + -3x = -1 + 0 -2 + -3x = -1 Add '2' to each side of the equation. -2 + 2 + -3x = -1 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = -1 + 2 -3x = -1 + 2 Combine like terms: -1 + 2 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333
| -84=-7(2m+6)+8m | | 1.5x+(18-1.5x)=18 | | X^3-125/5x-5 | | (5x+14y)+(3x+3y)= | | 700=464+7x | | -51+3= | | 7u-9=3u+5 | | X^3-135/5x-5) | | 3t-8=-11 | | x/3-6=10 | | y-18+y+x=180 | | 7x-5=-2x+4 | | -2y+14=3x | | 6h+5(3)=45 | | 5x+3(x-4)+12=2(4x+3) | | 2x+14=3x-31 | | 9r-9=-342 | | 4/3x-10=24 | | 7k-8(10)=45 | | -4=-9+v | | 4b-7=101 | | 45(n+6)=35n | | 2.56=x/2 | | -7=w+8 | | 2p+7=-53 | | (Y/6)4 | | 4x+1x+25+3x-5=2y-12 | | 8(9)+7a=79 | | 4c+6=-130 | | 5x-26=3x+20 | | 3+2(x+2)=9+3x | | (Y/-15)5 |